Mobile online services and measuring user satisfaction: study of Kuwait - Shah, Asadullah; Alzabi, Tami (IEEE, 2015)
User satisfaction is the key of success for any company to succeed and flourish business. Due to tremendous competition among service providers in the online sectors, many competitors feel threaten to be marginalized and loose competitive edge, and so is the profit margin. For many companies to survive business in a highly competitive environment, user satisfaction may be such factors to achieve lead over others. User satisfaction is a strong construct that emphasize on factors such as information quality, system quality, and service quality as its key parameters. This study aims to measure user satisfaction for online services provided by mobile companies in Kuwait and to develop a multi-scale model and assess its applicability in Kuwait scenario. This study involves exploratory factor analysis method to measure user satisfaction. The result showed that service quality, system quality, information quality are apex variables for user satisfaction for companies who compete in Kuwait in telecom sector.